Investigation of formation variation of portal vein with multidetector computed tomography - Bolatli, Gunes; Ulusoy, Mahinur; Koplay, Mustafa; Acar, Musa; Zarasiz, Ismail (International Journal of Research in Medical Sciences, 2019)
Background: To determine the types, frequency and clinical implications of formation of variations of portal vein with routine abdominal multi detector CT. Methods: MDCT images of 265 patients without any pathology were evaluated. Types and frequencies of formation variations of portal vein were determined. Results: Portail vein formation variations were observed in 186 (70.15%) of our study population. Normal portal vein was detected in 79 (29.8%) images. These variations were classified according to frequency. Normal anatomic structure was determined as type 1. Type 1 was observed in 79 (29.8%) images. As type 2 variation, left gastric vein flows into splenic vein instead of portal vein (60.75%). The type 3 of portal vein variation as uniting of superior mesenteric vein, inferior mesenteric vein and splenic vein at the same trunk to form portal vein was determined 9.43%. Conclusions: This study, which was performed to determine the anatomical variations of portail vein, makes the type 2 variation rate higher than the other studies. This information is different from the classical anatomy information. In addition, we are able to make the radiologists and surgeons highly capable of both recognition and functionality of the results.